A highly specific Escherichia coli qPCR and its comparison with existing methods for environmental waters. (1st December 2017) - Walker, David I.; McQuillan, Jonathan; Taiwo, Michael; Parks, Rachel; Stenton, Craig A.; Morgan, Hywel; Mowlem, Matthew C.; Lees, David N.
Abstract: The presence of Escherichia coli in environmental waters is considered as evidence of faecal contamination and is therefore commonly used as an indicator in both water quality and food safety analysis. The long period of time between sample collection and obtaining results from existing culture based methods means that contamination events may already impact public health by the time they are detected. The adoption of molecular based methods for E. coli could significantly reduce the time to detection. A new quantitative real-time PCR (qPCR) assay was developed to detect the ybbW gene sequence, which was found to be 100% exclusive and inclusive (specific and sensitive) for E. coli and directly compared for its ability to quantify E. coli in environmental waters against colony counts, quantitative real-time NASBA (qNASBA) targeting clpB and qPCR targeting uidA . Of the 87 E. coli strains tested, 100% were found to be ybbW positive, 94.2% were culture positive, 100% were clpB positive and 98.9% were uidA positive. The qPCR assays had a linear range of quantification over several orders of magnitude, and had high amplification efficiencies when using single isolates as a template. This compared favourably with qNASBA which showed poor linearity and amplification efficiency. When the assays were applied to environmental water samples, qNASBA was unable to reliably quantify E. coli while both qPCR assays were capable of predicting E. coli concentrations in environmental waters. This study highlights the inability of qNASBA targeting mRNA to quantify E. coli in environmental waters, and presents the first E. coli qPCR assay with 100% target exclusivity. The application of a highly exclusive and inclusive qPCR assay has the potential to allow water quality managers to reliably and rapidly detect and quantify E. coli and therefore take appropriate measures to reduce the risk to public health posed by faecal contamination. Graphical abstract: Image 1 Highlights: A new, 100% inclusive and exclusive qPCR method for E. coli was developed. qNASBA was found to be unsuitable for detecting E. coli in environmental waters. qPCR methods were found to correlate well with culture based methods in most cases.